Analysis of The Utilization of Religious Sentiments in Political Parties in The Pilkada Campaign in Sidoarjo - Rahma Safitriana; Agus Machfud Fauzi (Jurnal Sosiologi Agama, 2025)
This research analyzes the utilization of religious sentiment in the political campaign strategies of local political parties during the regional head elections (Pilkada) in Sidoarjo. The study employs a qualitative field research method through in-depth interviews, media content analysis, and observation. The purpose is to explore how religious symbols, narratives, and identity politics are mobilized to gain political legitimacy and mass support. In particular, the study focuses on how candidates strategically employ religious expressions, such as references to Islamic values, practices, and symbols, to resonate with voters, especially in a region where religion plays a significant role in social and cultural life. The results show that several political parties in Sidoarjo intentionally used religious issues, particularly those tied to Islamic values and institutions, as campaign tools. These strategies include invoking Islamic symbols, securing endorsements from religious leaders, and framing political discourse within religious narratives to appeal to religious sentiment. It has significant implications for the democratic process, raising concerns about the potential polarization of society and the manipulation of religious identity for political gain. Additionally, such practices may impact religious harmony in the region, as political parties exploit religious sentiments to consolidate their voter base. Theoretically, this study contributes to the discourse of political sociology and the sociology of religion by highlighting how religion is instrumentalized in contemporary electoral politics providing insights into the intersection of religion and political strategy in local governance.